L’ENJEU DE LA FONCTION PHATIQUE DANS LES INTERACTIONS VERBALES Cas des appels téléphoniques d’un centre d’appels - Chabour, Hanane (Journal of Human Sciences, 2016)
This study focuses on the importance of the phatic function in verbal interactions. This is the analysis of verbal exchanges through telephone calls in a call center, putting the sale of insurance and uses in its approach the so-called "forcing". The latter is to keep as long as possible prospects online and try to convince them to buy and all this through the phone. The results demonstrate the effective role of the phatic function in the smooth communication.